Strategi Komunikasi Publik Melalui Media Publisitas Universitas Muslim Indonesia Makassar dalam Penyebaran Informasi Program Merdeka Belajar Kampus Merdeka Tahun 2021 - Algiwity , Delza; Majid, Abd; Muttaqin, Andi (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
This thesis aims to determine the role of Public Relations of the Indonesian Muslim University Makassar in the MBKM (Merdeka Belajar Kampus Merdeka) 2021 program, to determine the public communication strategy of the Public Relations of the Indonesian Muslim University Makassar in disseminating information through publicity media related to the MBKM Program. This research uses a descriptive qualitative method using the theory of cybernetic traditions, communication goals and excellence in public relations, by determining informants in a proposive manner, namely the Head of the Public Relations Section, Public Relations Practitioners and also students who act as target audiences of the publicity media. The results of this research show that the Public Relations of the Indonesian Muslim University of Makassar responds to the MBKM program and has a strategy on disseminating information through publicity media. The response given was divided into two, namely structurally and culturally, by adapting the MBKM program into curriculum integrity for students of the Indonesian Muslim University of Makassar, but it did not run optimally. The strategy carried out by the Public Relations and Protocol of UMI Makassar refers to G-P-A activities, namely Goals, Plans, and Actions. Keywords